THE ELECTRICAL CHARACTERISTICS OF A CATENARY SYSTEM IN ELECTRIC RAIL VEHICLES, THE CALCULATION OF TRACTION LOAD AND SHORT – CIRCUIT CURRENTS - Kruczek, Włodzimierz (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Electrical railway vehicles need a reliable power source to comply with their designed specification. The specific working range of the electric traction system includes the big changes in the load during operation. A big power consumption in conjunction with the insufficient network can cause the loss of the vehicle's power. This problem is also addressed by the interoperability specification. The MATHCAD is used mainly for numerical calculations. The program simulates network with two power substations and two track sectioning cabins. It can also calculation single-sided network. The calculation step can be set from 1 m up to 1000 m. This is important for networks containing sections of different resistance. The calculation can be performed in three different variations: with constant current, constant vehicle resistance and with the set vehicle's speed and parameters. It is also capable of calculating the short-circuit current. The program interface enables the user unfamiliar to MATHCAD to perform the calculations. The user needs only to input data to pre-defined fields and tables. The results can be exported into other programs.